1977
DOI: 10.1136/bmj.1.6063.762
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric home nursing scheme in Gateshead.

Abstract: A scheme to provide specialised nursing care for sick children in their own homes was begun in Gateshead in 1974. Selected district nurses were retrained in the paediatric unit on which the scheme was based and nursed at home 22 children referred to them by general practitioners as the alternative to hospital admission and 39 discharged to their care by the hospital. Most of the children were aged 3 years or less and came from working-class homes. Most of the mothers who were asked were in favour of the scheme. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Notably also—the psychosocial concerns faced by the patient and the family in the transition from the hospital to the home environment Paediatric bone marrow transplantation 83 patients, of whom 56 had leukaemia, 13 had aplastic anaemia and 14 had SCID Thematic analysis Fuji et al, 2013 [ 15 ] USA Focus group discussions Perceptions of care transitions, their role within the process, barriers to effective care transitions and strategies to overcome these barriers Unclear 18 patients and/or caregivers, 13 hospital-based providers, 7 non-physician community providers Content analysis Hally et al, 1977 [ 16 ] UK Multi-methods—quantitative data, interviews, questionnaires Describe a home nursing scheme Paediatric home nursing scheme 53 (of 61 eligible) families, 18 GPs from six practices and number of nurses unclear (?4) Descriptive Sartain et al, 2000 [ 17 ] UK Semi-structured interviews, augmented with drawing techniques for children To explore children’s parents’ and health professionals’ experience of childhood chronic illness Other paediatric chronic condition with potentially life-threatening exacerbations 6 children, 10 parents and one healthcare professional associated with each family Grounded theory Sartain et al, 2001 [ 18 ] UK Structured and semi-structured interviews Experiences of hospital and home care Hospital at home service 11 children age 5–12 (6 hospital care, 5 hospital at home). Parents—20 in hospital care, 20 in hospital at home Content analysis Smith and Daughtrey, 2000 [ 19 ] UK Semi-structured interviews To identify any gaps in nursing services for acutely sick children and their families following discharge and to suggest ways to improve integration and communication between hospital and primary care to facilitate a ‘seamless web of care’ for families Children’s ward in medium sized DGH with both medical and surgical patients 20 parents who had needed help/support from a healthcare professional in the first 48 h following discharge ‘Burnard’s (1991) method for analysing interview transcripts in qualitative research’ Tatman et al, 1992 [ 20 ] UK Semi-structured interviews and questionnaires Views of parents and GPs of ...…”
Section: Resultsmentioning
confidence: 99%
“…Notably also—the psychosocial concerns faced by the patient and the family in the transition from the hospital to the home environment Paediatric bone marrow transplantation 83 patients, of whom 56 had leukaemia, 13 had aplastic anaemia and 14 had SCID Thematic analysis Fuji et al, 2013 [ 15 ] USA Focus group discussions Perceptions of care transitions, their role within the process, barriers to effective care transitions and strategies to overcome these barriers Unclear 18 patients and/or caregivers, 13 hospital-based providers, 7 non-physician community providers Content analysis Hally et al, 1977 [ 16 ] UK Multi-methods—quantitative data, interviews, questionnaires Describe a home nursing scheme Paediatric home nursing scheme 53 (of 61 eligible) families, 18 GPs from six practices and number of nurses unclear (?4) Descriptive Sartain et al, 2000 [ 17 ] UK Semi-structured interviews, augmented with drawing techniques for children To explore children’s parents’ and health professionals’ experience of childhood chronic illness Other paediatric chronic condition with potentially life-threatening exacerbations 6 children, 10 parents and one healthcare professional associated with each family Grounded theory Sartain et al, 2001 [ 18 ] UK Structured and semi-structured interviews Experiences of hospital and home care Hospital at home service 11 children age 5–12 (6 hospital care, 5 hospital at home). Parents—20 in hospital care, 20 in hospital at home Content analysis Smith and Daughtrey, 2000 [ 19 ] UK Semi-structured interviews To identify any gaps in nursing services for acutely sick children and their families following discharge and to suggest ways to improve integration and communication between hospital and primary care to facilitate a ‘seamless web of care’ for families Children’s ward in medium sized DGH with both medical and surgical patients 20 parents who had needed help/support from a healthcare professional in the first 48 h following discharge ‘Burnard’s (1991) method for analysing interview transcripts in qualitative research’ Tatman et al, 1992 [ 20 ] UK Semi-structured interviews and questionnaires Views of parents and GPs of ...…”
Section: Resultsmentioning
confidence: 99%
“…Hally et al . (1977 ), reporting on the development of a Model 3 team, emphasized that the GP retained clinical responsibility for the child in the home care scheme.…”
Section: Relevant Factors In Service Provisionmentioning
confidence: 99%
“…Early CCN schemes recognized the value of speci®c paediatric training for the community nurses involved in the schemes, e.g. Hally et al (1977) reported that each community nurse was retrained in the paediatric ward prior to setting up the CCN service. Alternatively Atwell & Gow (1985) discussed the role of the paediatric nurse who is community trained.…”
Section: Quali®cations Of Ccn Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence also suggests that children under 5 years of age and those having multiple admissions (Quinton & Rutter 1976) are particularly susceptible to the injurious effects of hospitalization. The development of alternatives to hospitalization have therefore proved attractive, not only to avoid the deleterious consequences of hospitalization but also because they have the potential to maximize the use of health care resources (Hally et al 1977, Couriei & Davies 1988 and reduce the incidence of hospital-acquired infections (Atwell & Gow 1985, Couriei & Davies 1988.…”
Section: Introductionmentioning
confidence: 99%